ANALYSIS OF HEART FAILURE MEDICAL TREATMENT COST AS THE CONSIDERATION IN DETERMINING THE HEALTH COST DUE TO INA-DRGs AT RSUD Dr. MOEWARDI SURAKARTA - Vivin Rosvita; Zullies Ikawati; Achmad Purnomo (Faculty of Pharmacy, Universitas Gadjah Mada)
The implementation of INA-DRG for Jamkesmas Class III patient at the hospital was expected to be able to increase the access and quality of health service to the poor in order to realize the optimal health service effectively and efficiently. The aims of this research were to analyze the medical cost of heart failure patients, to investigate the affect of patient’s factors, comorbidities, severity level and the duration of treatment on the cost of heart failure treatment and to investigate the difference of average cost for the heart failure patient’s treatment based on the rate of RSUD Dr. Moewardi with the rate of INA-DRG package. This research was descriptive according to the hospital perspective. The data collection method conducted retrospectively. The research subject was the patients who were hospitalized in class 3 and the member of Jamkesmas at RSUD Dr. Moewardi at period of 2009 who suffered from heart failure and fulfilled the inclusive requirement. The data analysis was done with cross tab and linear regression, the cost average comparison and LOS from INA-DRGs package. The p values of statistic result test among sex, age, number of comorbid, severity level and LOS on the medical cost were 0.851, 0.960, 0.694, 0,0621 and 0.000. The average of heart failure medical cost based on RSUD Dr. Moewardi rate on the level of severity I was Rp. 1,870,231 ± Rp.1,506,661, while on the level of severity II was Rp. 2,382,737 ± Rp. 2,132,236 and on the level of severity III was Rp. 2,513,826 ± Rp. 1,664,057. Real ALOS on the level of severity I was 6.92 days, while on the level of severity II was 7.35 days and on the level of severity III was 8.10 days. The research result shown that there was no relation between the patient’s character, number of comorbid and severity level on the hospital medical cost, while the treatment duration had corelation with the medical cost. The average of heart failure treatment cost on the level of severity I, II, and III was lower compared to INA-DRG package rate. It shown that the hospital succeeds to use medical facilities efficiently so that the tarrif will not surpass it of INA – DRG, while the difference of real ALOS and ALOS INA-DRG was the highest on the level of severity III. It has showed that the hospital has done efficiency and has been able to decrease the duration of the heart failure inpatient treatment at the hospital.Key words: INA-DRG, heart failure, Jamkesmas